Application of a pre-targeting drug delivery system for precise treatment of breast and ovarian cancer - Zhang, Chaoyu; Justus Liebig University Giessen (My University, 2023)
The target therapy has ushered in a new generation of cancer treatment, but it still confronts to some limitations, for example, most of the mAbs lack enough cytotoxicity to be translated into clinical fruition. The ADC comes of age as a novel and promising antineoplastic therapy on the grounds that it combines the specificity of mAb and potent toxicity of small molecules. As the cytotoxicity of ADCs mainly comes from the payload rather than mAb, it allows more mAbs to be applied into target therapy and also endows the possibility of these small molecules to be used in patients. Although the approved ADCs have achieved tremendous success in clinical outcomes, still there are obstacles such as the low accumulation in tumor site, off-target cytotoxicity and heterogeneous products after conjugation. To overcome these problems and optimize the ADC design, a pre-targeting drug delivery system was established in this study. The pre-targeting system is based on the specific interaction between a pair of synthetic coiled coils proteins named Zip1 and Zip2. Compared to the conventional drug delivery system, the two-step drug delivery approach, first, is designed to reduce the size of the antibody to improve the tissue penetration so the antibodies are more likely to reach the deep-seated tumor. Second, in virtue of the small size of the Zip1-labeled effector molecule, the pre-targeting system is supposed to accelerate the accumulation of drug in the target site and increase the tumor/nontumor ratio of drug by fast clearance of the excess effector molecules in the circulation. Additionally, a site-specific conjugation method using the SNAP-tag was introduced to achieve effortless and rapid labelling and also to produce homogeneous product. To evaluate the potential of the pre-targeting system for drug delivery, functional assays were carried out. The specific interaction between the Zip1 and Zip2 was confirmed by far-western blotting, and the EGFR-, EpCAM-, Her2- and Trop2-specific pre-targeting complex exhibited the rapid and high specific drug or fluorescence delivery ability as well as the comparable cytotoxicity with direct conjugation in breast cancer and ovarian cancer cell lines. However, the in vivo experiment which is not involved in this study should be further performed to assess the therapeutic and safety property and in vivo efficacy. In conclusion, this study firstly demonstrated the pre-targeting drug delivery system using scFv, SNAP-tag technology and interaction between coiled coils. Even though this pre-targeting drug delivery system was just assessed in breast and ovarian cancers, the application is never limited in these four antigens or in these two cancer types. This novel drug delivery system can be broadened to treat various types of cancers, target suitable tumor associated antigens and bearing different BG-modified drugs.
Keywords: ddc:610